SINTESIS DAN UJI TOKSISITAS SENYAWA METOKSI FLAVANON TURUNAN 2â-HIDROKSIKALKON - Rizal, Syamsul; Zamri, Adel (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Flavanone is one of secondary metabolities included into flavonoid group that has biological activities such as anticancer, antitumor, antiproliferative, and antimicrobe. Moreover, flavanone is the biosynthesis main precursor for other types of flavonoids. In this research, 4â-methoxyflavanone has been synthesized from cyclization of 2â-hydroxychalcones derivatives by microwave irradiation using sodium acetate in ethanoland water as a catalyst. The yield obtained was 68,5 %. The purity of compound has been tested using TLC, melting point test, and HPLC. The compound was characterized by UV, IR,1 H-NMR, and MS. Toxicity activity was determined using Brine Shrimp Lethality Test (BSLT) against larvae of Arthemia salina Leach and with value LC50 = 3,29 Âµg/ mL. Accordings to the primary test, the flavanone compound is potentially as anticancer which was proven by LC 50 values <200 Î¼g/mL.